Clinical Profile of Patients with Recurrent Seizure in Tertiary Care Hospital in Nepal - Kafle, DR; Oli, KK (Kathmandu University Medical Journal, 2015)
Background Epilepsy is a common and diverse disorder with many different causes. Outcomes are varied with 60—70% of newly diagnosed people rapidly entering remission after starting treatment and 20—30% developing a drug-resistant epilepsy with consequent clinical and psychosocial distress. About one third of patients with a first unprovoked seizure will have further seizures within five years, and about three quarters of those with two or three unprovoked seizures have further seizures within four years. Objective The aim of the study was to find out those factors which were associated with recurrence of seizure in Nepalese population. Method It is a Descriptive Cross-sectional study which was conducted in Tribhuvan University Teaching Hospital from January 2013 to January 2014. Result A total of 150 patients participated in the study. Neuroimaging was normal in 65(43.3%) patients. 48(32%) patients had neurocystercosis in their brain imaging, neuroinfection in 12(8%) of cases, cerebral infarction in 12(8%), Cerebral atrophy in 5(3.3%) patients, brain tumor in 4(2.7%), Mesial temporal sclerosis in 2(1.3%), tuberous sclerosis in 1(0.7%) and hypoxic brain injury in 1 (0.7%) patient. 14(9.3%) patients reported having a family history of epilepsy in first degree relative. There was statistically significant association between higher number of seizures before starting medication and increased frequency of seizure after starting medication (p<0.001). Conclusion Most of the patients with recurrent seizure had identifiable cause. Neurocysticercosis was the most common cause. Higher number of seizure before starting medication was associated with increased frequency of seizure after starting medication. Kathmandu University Medical Journal Vol.12(3) 2014; 202-206